THE EFFECT OF EDUCATIONAL GAMES ON THE ANGER LEVELS OF MENTALLY DISABLED CHILDREN - ZENGİN, Serkan; PEKER, Alper Tunga (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
Aim of this study is to examine the effects of educational games on the anger levels of mentally disabled children. First grade 56 disabled children in age of 8 - 15 who are studying at the Ağrı special education practicing center that is affiliated with directorate of national education located at Ağrı province, participated into the research. Children were randomly selected and divided into two groups as test group and control group. While education game studies were applied on the test group for 3 hours in one day of the week for 8 weeks, the control group only continued its studies in the special education center. Anger scale and anger expression scale were applied on the parents of subjects in the pre-study and post-study process. It was determined that data showed normal distribution by making normality test. Two-paired samples T test was used in intra-group comparisons, independent T test was used in the intergroup comparisons. Margin of error was regarded as 0.05 in this study. When the findings obtained were examined; a statistically significant difference could not be found between the last test results of test and control groups. On the other hand, a statistically significant difference could not be found between the pretest posttest results of the test group, however, when pretest-posttest test results of the control group regarding continuous anger and extrinsic anger state were compared, it is seen that posttest results are significantly higher (P<0,05). In the comparison of pretest-posttest test results of the test group and control group in terms of disability condition, a statistically significant difference could not be found between pretest-posttest test results of individuals who have two types of disability in the test group. On the other hand, when continuous anger and extrinsic anger means of autistic individuals in the control group were examined, it is seen that posttest test results are higher at a statistically significant extent (P<0.05).